Effect of electromagnetic boundary conditions on the onset of small-scale dynamos driven by convection - Fontana, Mauro (2023)
We present a high-order numerical study of the dependence of the dynamo onset on electromagnetic boundary conditions in convecting Boussinesq flows forced by temperature gradients. Perfectly conducting boundaries, vacuum, and mixed boundary conditions are considered, treating fields and boundary conditions with close to spectral accuracy. Having one or two conducting boundaries greatly facilitates dynamo action. For the mixed case it is shown that the critical magnetic Reynolds number becomes independent of the Rayleigh number Ra for sufficiently large Ra.